Twenty Years Post-Iraq: Neoconservatism from the Ethereal into the Room - Eshanasir, Rifqy Tenribali (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
Over twenty years after the controversial 2003 Iraq War, there has been several academic foreign policy analyses into what factors influenced United States (US) President, George Bush, and his administration’s decision to invade Iraq. Investigations into influential factors behind critical decisions made on behalf of the state like this can be called ‘Foreign Policy Analysis’ and is done to understand and potentially predict similar decisions in the future. Regarding the 2003 Iraq Invasion, different Scholars emphasise domestic-level factors, including US bureaucratic politics, media and public opinions, the interests of US neoconservatives or national culture and identity. Additionally, some scholars emphasise international-level factors, namely the importance of oil for the US and the influences of the global balance of power. This article argues a combination of neoconservative interest groups, US bureaucratic politics, and small-group dynamics especially influenced President Bush’s invasion decision. Specifically, neoconservative interest groups navigated US bureaucratic politics to gain high governmental positions and influenced small-group dynamics, limiting President Bush’s perception of alternatives and ultimately deciding to invade Iraq. The article proposes an explanatory narrative for the Iraq War, exploring neoconservatism’s journey as an intangible idea, to being institutionalised, and making its way into President Bush’s inner circle through certain individuals.Keywords: Bureaucratic Politics, Foreign Policy Analysis, Interest Groups, Iraq War, Small-Group Dynamics.Lebih dari dua puluh tahun setelah Perang Irak yang kontroversial pada tahun 2003, terdapat beberapa analisis mengenai faktor-faktor yang mempengaruhi keputusan Presiden Amerika Serikat (AS), George Bush, dan pemerintahannya untuk menginvasi Irak. Para ahli menekankan pentingnya faktor-faktor di tingkat dalam negeri (domestik), termasuk politik birokrasi AS, media dan opini publik, kepentingan kaum neokonservatif AS, maupun budaya dan identitas nasional negara tersebut. Beberapa ahli juga menekankan faktor-faktor di tingkat internasional, misalnya pentingnya minyak bagi AS dan pengaruh keseimbangan kekuatan global. Artikel ini berargumentasi bahwa kombinasi kelompok kepentingan neokonservatif, politik birokrasi AS, dan dinamika kelompok kecil berperan penting dalam mendorong Keputusan Presiden Bush untuk menginvasi Irak. Secara khusus, kelompok kepentingan neokonservatif memanfaatkan politik birokrasi AS demi mendapatkan posisi yang tinggi dalam pemerintahan dan mempengaruhi dinamika kelompok kecil yang kemudian membatasi persepsi Presiden Bush dari alternatif lain dan mendorongnya memutuskan untuk menyerang Irak. Artikel ini menawarkan narasi penjelas mengenai Perang Irak yang mengeksplorasi perjalanan neokonservatisme dari sebuah ide yang tidak berwujud, menuju ide yang terlembagakan, dan kemudian masuk ke lingkaran dalam Presiden Bush melalui individu-individu tertentu.Kata-kata Kunci: Politik Birokrasi, Analisis Kebijakan Luar Negeri, Kelompok Kepentingan, Perang Irak, Dinamika Kelompok Kecil.